2011
DOI: 10.1182/blood-2011-03-341073
|View full text |Cite
|
Sign up to set email alerts
|

SHP-1 expression accounts for resistance to imatinib treatment in Philadelphia chromosome–positive cells derived from patients with chronic myeloid leukemia

Abstract: We prove that the SH2-containing tyrosine phosphatase 1 (SHP-1) plays a prominent role as resistance determinant of imatinib (IMA) treatment response in chronic myelogenous leukemia cell lines (sensitive/ KCL22-S and resistant/KCL22-R). Indeed, SHP-1 expression is significantly lower in resistant than in sensitive cell line, in which coimmunoprecipitation analysis shows the interaction between SHP-1 and a second tyrosine phosphatase SHP-2, a positive regulator of RAS/MAPK pathway.In KCL22-R SHP-1 ectopic expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
43
2
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 41 publications
5
43
2
1
Order By: Relevance
“…There was no clinically relevant pharmacokinetic interaction between veliparib and temozolomide and the pharmacokinetics appeared to be linear, similar to single-agent studies in solid malignancies (37, 38). This is in contrast to our study of veliparib plus topotecan/carboplatin in poor-risk myeloid malignancies, where non-linear pharmacokinetics were observed above veliparib doses of 80 mg twice daily for 9–14 days (39). A possible explanation for the difference in pharmacokinetics between the two regimens could be an impact of topotecan/carboplatin on renal elimination, resulting in prolonged veliparib exposure (38, 40) that is not seen with temozolomide.…”
Section: Discussioncontrasting
confidence: 99%
“…There was no clinically relevant pharmacokinetic interaction between veliparib and temozolomide and the pharmacokinetics appeared to be linear, similar to single-agent studies in solid malignancies (37, 38). This is in contrast to our study of veliparib plus topotecan/carboplatin in poor-risk myeloid malignancies, where non-linear pharmacokinetics were observed above veliparib doses of 80 mg twice daily for 9–14 days (39). A possible explanation for the difference in pharmacokinetics between the two regimens could be an impact of topotecan/carboplatin on renal elimination, resulting in prolonged veliparib exposure (38, 40) that is not seen with temozolomide.…”
Section: Discussioncontrasting
confidence: 99%
“…We proved that regorafenib directly targets SHP-1 to inactivate the STAT3-mediated signaling pathway and induces anti-HCC activity in vitro and in vivo, suggesting that SHP-1 may be a druggable protein for the treatment of HCC. Similarly, Nicola and colleagues (15) reported that SHP-1 expression determines the resistance to imatinib for chronic myelogenous leukemia treatment and lower levels of SHP-1 were also found in patients with imatinib treatment failure. In light of these findings and this study, we propose that patients with HCC with lower expression of SHP-1 may be more resistant to regorafenib than those patients with higher SHP-1 expression.…”
Section: Discussionmentioning
confidence: 87%
“…They regulate a variety of cellular processes including cell growth, differentiation, oncogenic transformation and the mitotic cycle. SHP-1 is expressed in normal lymphoid cells, but is lost in a number of types of hematologic malignancies due to epigenetic silencing (45,46). It has been demonstrated that loss of SHP-1 directly contributes to the constitutive activation of STAT3 in MM, chronic myeloid leukemia and anaplastic lymphoma kinase-positive anaplastic large cell lymphoma (47).…”
Section: Discussionmentioning
confidence: 99%